Pengaruh Experiential Marketing Dan Kepuasan Terhadap Loyalitas Pelanggan Dengan Kepercayaan Sebagai Variabel Moderator (Studi Pada Pengguna Aplikasi KAI Access Di Surabaya) - Nobmadella, Oviradita; ,, Nurhadi (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
There are several train ticket service applications as official partners of PT. KAI on Android and iOS devices such as Traveloka, Tiket.com, Pegipegi which can spur the competition to offer its advantages. Therefore, the KAI Access application must be able to provide the best experience, satisfaction, and trust so that users remain loyal and provide positive reviews. This study aims to determine: (1) The effect of experiential marketing and satisfaction on customer loyalty, (2) The role of trust in moderating the effect of experiential marketing and satisfaction on customer loyalty. The population of this study were users of the KAI Access application in Surabaya. This study, used a sample of 384 respondents. The sampling technique is a purposive sampling technique with the criteria of KAI Access application users who are domiciled in Surabaya, aged + 17 years, and have purchased train tickets on the KAI Access application at least once. The data analysis techniques used Partial Least Square with the software of SmartPLS 3.0. The results of this study indicates that experiential marketing and satisfaction has a positive and significant effect on customer loyalty, trust moderates the effect of experiential marketing and satisfaction on customer loyalty.